Telling Another Story of Europe: A Reply in Favour of Politics - Middelaar, Luuk van (BMGN - Low Countries Historical Review, 2010)
Middelaar, Luuk van, De passage naar Europa. Geschiedenis van een begin (Dissertatie Universiteit van Amsterdam 2009; Groningen: Historische Uitgeverij, 2009, 531 blz., ISBN 978 90 6554 236 6). All three discussiants note the rich use of language in De passage naar Europa, but without linking it to the book’s discourse analysis or its alleged scarcity of social science. Words are not innocent, however; in political battles, even theoretical concepts are constantly being co-opted. To escape from existing connotations, we can either examine a vocabulary’s use (a well-known practice in intellectual history), or introduce new words (as I do with ‘passage’ or ‘sphere’). For good reason, history, political philosophy and law are the disciplines chosen to tell this story of Europe. The focus is neither on the Brussels institutions, nor just on Member States and national interests. Rather, it is the story of the ensemble of European states trying to become the political expression of the continent: of its birth and metamorphoses, its efforts to fill a space and find a voice. This review is part of the discussion forum 'De passage naar Europa. Geschiedenis van een begin' (Luuk van Middelaar).